User-oriented development trends: SL USARB electronic catalog (Confluenţe Bibliologice, 2022)
The article reflects the evolution and importance of library catalogs, the need for the emergence of a shared electronic catalog. The capabilities of the shared electronic catalog in terms of information search, its value in storing valuable information for teaching, study and research processes are highlighted.
Keywords: electronic catalog; search efficiency; user training; PRIMO search system